Sistem Penyiraman Tanaman Indoor Berbasis Sensor Suhu, Kelembaban, Dan Cahaya Menggunakan Logika Fuzzy Logic - Sudrajat Sudrajat; Rini Anggraeni; Nur Raudhah Fauziah; Zahra Syahty Putri; Yudistira Hartono Putra; Rizky Subagja; Denny Arief Rusamsi (Jurnal Indonesia Sosial Teknologi, 2025)
As one of the vegetable production centers in West Java, Indramayu Regency plays a crucial role in meeting market demand. However, farmers still face challenges in efficient use of water, time, and energy, particularly in the manual watering process. Furthermore, increasing awareness of healthy vegetable consumption without pesticide exposure encourages people to cultivate plants independently indoors. Indoor cultivation is chosen as a solution when land availability is limited and environmental conditions do not support optimal plant growth. This study aims to design and implement an automatic watering system based on Mamdani fuzzy logic for indoor cultivation of mustard greens (Brassica rapa). This system uses an ESP32 microcontroller integrated with a soil moisture sensor (Soil Moisture), a temperature sensor (DS18B20), and a light intensity sensor (GUVA-S12SD), and is equipped with a UV Growlight lamp configured to operate for 20 hours per day to support photosynthesis in conditions of low natural light. The watering process is adaptively regulated based on environmental parameters using fuzzy logic, while system monitoring and control are performed in real time via the Node-RED platform with MQTT-based data communication. Test results show that the system can efficiently adjust watering frequency and duration, support optimal plant growth, and facilitate remote monitoring. This system is considered efficient for urban agriculture and households with limited land.